AGGRESSIVE AS AMOTIV FACTOR OF TERRORUSM - N.S. SEDICH (Advanced Engineering Research)
Agvession as a motive factor of terrorism and sexual differences in terrorism motive. These is the principal difference between mens and womens terrorism. From the mens point of view terror is a way of getting economic and political supremasu, but from the womens point of view terror is a way of self realization, a way of getting the sense of power and control and a way of rising one’s social status.